2018
DOI: 10.30544/244291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the fabrication process of copper matrix composites on cavitation erosion resistance

Abstract: Copper matrix composites reinforced with ZrB2 particles were produced in two ways: by hot pressing (HP) and laser-sintering process. Powder mixture Cu-Zr-B was mechanically alloyed before densification processes. Variations in the microstructure of treated samples obtained during cavitation test were analyzed by scanning electron microscopy (SEM). Cavitation erosion resistance was investigated with the standard test method for cavitation erosion using vibratory apparatus. Changes in mechanical alloying duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Alloys are obtained in the form of foils through GCLS and 3D pieces through selective laser melting layer-by-layer. An innovative approach, contained of mechanical alloying and pulsed-SLM processes, was used for manufacturing copper-based composites with the aim to improve their wear resistance [42]. The study reported that laser-sintered samples show better cavitation erosion resistance compared to samples obtained by powder metallurgy (densification did by hot pressing).…”
Section: Laser Melting/sinteringmentioning
confidence: 99%
“…Alloys are obtained in the form of foils through GCLS and 3D pieces through selective laser melting layer-by-layer. An innovative approach, contained of mechanical alloying and pulsed-SLM processes, was used for manufacturing copper-based composites with the aim to improve their wear resistance [42]. The study reported that laser-sintered samples show better cavitation erosion resistance compared to samples obtained by powder metallurgy (densification did by hot pressing).…”
Section: Laser Melting/sinteringmentioning
confidence: 99%